Marine Protected Area Policy Networks as a Catalyst for Local Resilience: Evidence from Eastern Bintan Island - Edison, Edison; Safitri, Dian Prima; Elsera, Marisa; Sucipta, Pery Rehendra; Ulqadri, Ulqadri (Journal Public Policy, 2025)
Marine Protected Areas (MPAs) are becoming an essential tool for marine biodiversity conservation and sustaining the livelihood of coastal communities. Nonetheless, the success of MPAs relies, to a great extent, on the efficiency of the policy networks that manage them. This research explores policy networks' role as drivers of local resilience in East Bintan Island, Indonesia. The objective of this research is to understand how policy networks and dynamics in MPA governance can support the social-ecological resilience of local communities. This study used a qualitative method design to identify the composition, dynamics, and effects of such networks and how they facilitate coordination among stakeholders, enhance the efficiency of resources, and solve social-ecological issues. The research established that policy networks in East Bintan Island have a transformative function of connecting government agencies, local communities, and non-government organizations. They facilitate knowledge, power, and resource sharing that optimizes adaptive capacity and enables sustainable practice. Yet, their complete potential is hampered by issues such as power imbalances, institutional obstacles, and conflicts of interest. This study makes a contribution to the literature by providing empirical insights into the catalytic function of policy networks in MPA governance. Additionally, it offers practical suggestions to practitioners and policymakers who aim to promote local resilience using adaptive and inclusive governance. Through the explanation of policy networks and their connection to community resilience, the study affirms that collaborative ecosystems are necessary as a reaction to socio-economic and environmental problems within the coastal region due to their complexity.